A general shock waveform and characterisation method. (February 2020) - Yan, Yinzhong; Li, Q.M.
Highlights: A general shock waveform is proposed, which can represent the pyroshock and mechanical shocks. Parameters in the waveform have their respective mechanical meaning. A decomposition method is proposed to represent the original shock using a series of the proposed waveform components. Applications to near-, mid- and far-field pyroshocks are demonstrated. Abstract: A shock waveform is proposed based on the mechanical mechanism of shock generation in a structure. The parameters in the shock waveform have clear mechanical meanings about the generation and development of the shock. A shock signal processing method is proposed and applied to represent a pyroshock or ballistic shock signal in both temporal and frequency domain using finite terms of the shock waveform components. It is found that the complexity of the shock and the dominant shock distance of a shock can be described quantitatively by the number of waveform components ( η 90 % ) and a normalised parameter ( κ ), respectively. Pyroshock and mechanical shocks in different categories are analysed using the proposed shock waveform to demonstrate its importance and generality in shock representation.